Pemanfaatan Podcast Sebagai Media Content Creator Dalam Meningkatkan Pengembangan Diri Mahasiswa - Sinta Yanwar Rosah; Nur Maghfirah Aesthetika (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Podcast is one of the results of radio development in the new media era. With te presence of podcasts in today`s increasingly sophisticated technological era, there are many positive impacts, one of which is helping students to be more creative in the audio visual field. This study uses the theory of social cognition about te self as a place where all communication messages can be centralized and easy to channel using internet technology and involve the audience to improve the process of interaction and communication. The purpose of this study is to measure ow much students use podcasts as content creators in self-development. This study uses a quantitative method of observation with data collection tecniques trough questionnaires. This method is used as a reference material to collect information and observations of a subject.  50% of respondns answered agree, 10% of respondents chose strongly agree, but 30% of respondents did not show interests. 5% of respondents` answers expressed doubts about the use of podcasts for sudents in improving interpersonal communication and 5% of respondents` anwers stated that they strongly disagreed with podcast media supporting podcasts as communicative media.